Tekanan Darah Pada Penderita Hipertensi Dapat Diturunkan Dengan Obat Tradisional (Musa Paradisiaca Var Sapientum Linn) - Mareyke Y. L Sepang; Calvin R. C Langingi; Ignatia Y. Rembet; Kansia Anastasia Terok (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Hypertension is a disease that can be prevented, but can cause various complications if not treated properly. Efforts to avoid these complications are carried out by managing hypertension properly and its management is carried out pharmacologically and non-pharmacologically. Non-pharmacologically, namely by consuming lots of fruits. Ambonese banana is one of the plants that are often found in Indonesia that contains potassium to lower blood pressure. The purpose of this study was to analyze the effect of Ambon Banana therapy in lowering blood pressure in patients with hypertension. This type of research is Pre-Experiment with One Group Pre-Test-Post-Test approach. This study provides intervention for hypertensive patients in the form of giving Ambon Bananas. The implementation of the intervention begins with a Pre-Test of blood pressure measurement, then the administration of Ambonese Banana intervention 1 time 2 for 6 days, then a Post-Test of blood pressure measurement is carried out. Sampling using probability sampling method with simple random sampling technique with a sample of 20 respondents. The results showed that Ambon Banana therapy lowered the blood pressure of hypertensive patients. After the intervention, systolic blood pressure drops. The results of the Mann Whitney statistical test obtained a value of p = 0.008 (<0.05) for systolic pressure, and diastolic blood pressure showed a value of p = 0.010 (<0.05) which means this study showed a significant relationship between giving Ambonese bananas and blood pressure